Synthesis and export of the outer membrane lipoprotein in Escherichia coli mutants defective in generalized protein export. - Watanabe, T (1988)
Export of the outer membrane lipoprotein in Escherichia coli was examined in conditionally lethal mutants that were defective in protein export in general, including secA, secB, secC, and secD. Lipoprotein export was affected in a secA(Ts) mutant of E. coli at the nonpermissive temperature; it was also affected in a secA(Am) mutant of E. coli at the permissive temperature, but not at the nonpermissive temperature. The export of lipoprotein occurred normally in E. coli carrying a null secB::Tn5 mutation; on the other hand, the export of an OmpF::Lpp hybrid protein, consisting of the signal sequence plus 11 amino acid residues of mature OmpF and mature lipoprotein, was affected by the secB mutation. The synthesis of lipoprotein was reduced in the secC mutant at the nonpermissive temperature, as was the case for synthesis of the maltose-binding protein, while the synthesis of OmpA was not affected. Lipoprotein export was found to be slightly affected in secD(Cs) mutants at the nonpermissive temperature. These results taken together indicate that the export of lipoprotein shares the common requirements for functional SecA and SecD proteins with other exported proteins, but does not require a functional SecB protein. SecC protein (ribosomal protein S15) is required for the optimal synthesis of lipoprotein.